Application of the Problem Based Learning (PBL) Model to Improve Student Learning Outcomes in Class V at UPTD SD Negeri Tapos 5, Depok City - Apit Dulyapit; Yayat Supriatna; Fanny Sumirat (Journal of Insan Mulia Education, 2023)
This study aims to determine student learning outcomes by using the Problem-Based Learning (PBL) Learning Model implemented with teachers at UPTD SD Negeri Tapos 5 Depok City. This research uses Classroom Action Research (PTK) developed by Kemmis and Mc Taggart which is carried out in stages through two cycles. Each cycle was carried out in stages from action planning, action implementation, observation/evaluation, and ended with reflection. The research subjects totaled 31 students who had different characteristics with the number of males 15 students and females 16 students. The stages are carried out according to the Problem-Based Learning (PBL) Learning Model procedure. The results showed that there was an increase in student learning outcomes as evidenced by the average in cycle I was 79.68 with a percentage of 75.94% increase in cycle II to 85.48 with a percentage of 83.80% with an increase of 7.86% in the "Very Good" category. Based on the findings during the research, it can be concluded that using the Problem-Based Learning (PBL) Learning Model can improve the learning outcomes of grade V students at UPTD SD Negeri Tapos 5 Depok City in science subjects on the material of vertebrate and invertebrate animal locomotion. These results are expected to have a positive impact on students and become an insight for teachers in carrying out learning activities at school.